Common Sense Diagrams: The US Two-Party System in Magruder’s American Government, 1917–2023 - Janne Holmén (Nordic Journal of Educational History)
This article investigates how the two-party system is analysed in text and diagrams in US government textbooks. The diagrams are analysed with the help of theories from the cognitive sciences. Magruder’s American Government has dominated the US civics textbook market since its first edition in 1917. That year, the textbook referred to “the four leading parties,” and the two-party system concept first appeared in a diagram in 1930. From 1939, the two-party system was considered a trait of English-speaking countries and was contrasted to the chaotic multiparty systems in Europe, which could end up in dictatorship. From the 1950s, the two-party system was explained as an effect of the electoral system and as a reflection of the lack of divisions in US society. Diagrams of the party system were gradually simplified until the 1990s, when they implied that Democrats and Republicans had unbroken roots in the late 1700s. From the 2010s, more critical explanations of the two-party system appeared, such as that the major parties issue legislation that hinder the formation of new parties.